Fin-Talk: Pelatihan Penyusunan Laporan Keuangan Untuk Umkm Melek Finansial - Fachmi Resya; Ardhitya Alam Wiguna; Dicky Andriyanto; Financia Mayasari; Ariza Arisandi (LPPPM STAI Darul Hikmah Bangkalan, 2026)
This community service activity aimed to encourage capacity building for MSME actors in Gebang Tunggul, Patrang District, Jember Regency, in managing business finances through training on simple financial statements based on SAK EMKM. A total of 20 participants with backgrounds in culinary arts, sewing, and services were involved as partners. The priority problems encountered included a lack of financial literacy understanding, the absence of separation between personal and business finances, and the inability to prepare financial statements. The activity was carried out using a participatory method consisting of three sessions: material presentation, problem-solving discussions, and direct practice in preparing financial statements accompanied by intensive mentoring. The initial assessment results showed that only 15% of participants kept simple financial records, and all participants were unfamiliar with the components of financial statements. After the activity, participants demonstrated a noticeable increase in understanding, particularly in separating financial records and preparing profit and loss statements. Participatory discussions successfully formulated solutions to technical obstacles such as calculating Cost of Goods Sold (COGS) and recording accounts receivable. As a sustainability measure, a communication group was formed and periodic monitoring was scheduled. Thus, this program is effective in equipping MSMEs with applicable and sustainable financial management competencies.